2013
DOI: 10.5194/acpd-13-23173-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Secondary organic aerosol formation exceeds primary particulate matter emissions for light-duty gasoline vehicles

Abstract: The effects of photochemical aging on emissions from 15 light-duty gasoline vehicles were investigated using a smog chamber to probe the critical link between the tailpipe and ambient atmosphere. The vehicles were recruited from the California in-use fleet; they represent a wide range of model years (1987 to 2011), vehicle types and emission control technologies. Each vehicle was tested on a chassis dynamometer using the unified cycle. Dilute emissions were sampled into a portable smog chamber and then photoch… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
98
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(112 citation statements)
references
References 52 publications
12
98
1
1
Order By: Relevance
“…As smog chamber studies indicate that SOA formed from photochemical aging of vehicle exhausts overwhelmingly dominate over the directly emitted primary organic aerosols (POA) (Nordin et al, 2013;Gordon et al, 2014;Liu et al, 2015), it is important to get a full spectrum of SOA precursors, including dicarbonyls, in the vehicle exhausts. From our tests in the Zhujiang Tunnel in urban Guangzhou, we obtained the EFs of glyoxal and methylglyoxal for on-road vehicles in China for the first time.…”
Section: Resultsmentioning
confidence: 99%
“…As smog chamber studies indicate that SOA formed from photochemical aging of vehicle exhausts overwhelmingly dominate over the directly emitted primary organic aerosols (POA) (Nordin et al, 2013;Gordon et al, 2014;Liu et al, 2015), it is important to get a full spectrum of SOA precursors, including dicarbonyls, in the vehicle exhausts. From our tests in the Zhujiang Tunnel in urban Guangzhou, we obtained the EFs of glyoxal and methylglyoxal for on-road vehicles in China for the first time.…”
Section: Resultsmentioning
confidence: 99%
“…Nordin et al [26] found that SOA formed from the exhaust of idling gasoline vehicles could be 1-2 orders of magnitude higher than POA. Gordon et al [18] and Platt et al [27] also observed an enhancement of SOA/POA from 1 to 15 during the aging of emissions from LDGVs. Significant nitrate and ammonium were observed to be formed synchronously with SOA during the photooxidation of LDGV exhaust [18,26].…”
Section: Introductionmentioning
confidence: 92%
“…Gordon et al [18] and Platt et al [27] also observed an enhancement of SOA/POA from 1 to 15 during the aging of emissions from LDGVs. Significant nitrate and ammonium were observed to be formed synchronously with SOA during the photooxidation of LDGV exhaust [18,26]. However, the formation of secondary aerosols including SOA, nitrate, and ammonium from vehicle exhaust still remain uncertain when NH 3 is removed.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations